THE USE OF TRIADIC SEMANTIC MODEL TO ANALYZE A DOCUMENTARY MOVIE :LION KINGDOM EPISODE 1: PRIDE AND PUNISHMENT - Zeffi Sugiharto; Windyana Monata; Hendra Husnussalam (IKIP Siliwangi, 2020)
Charles Sanders Pierce’s Triadic semantic model is a semiotic theory that analyze the signs according to the relationship of the represantament and the object. The semantic research on the documentary movie entitled Lion Kingdom, episode 1: Pride and Punishment shows that there are three signs used in the movie. (1) Icon signs, appears 3 times, (2) indexes signs (appears 17 times), and Symbols, appears 15 times. Keywords: semiotic, Charles Sanders Pierce’s, movie.